ECONOMIC GROWTH, FINANCIAL DEVELOPMENT AND STOCK MARKET: SECTORAL EVIDENCE FROM INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study undertaken aims to investigate the  effect of financial development and sector specific stock market indices on the respective  sector’s growth for the Indian economy and  uses quarterly time-series data ranging from  2005-06: Q1 to 2019-20: Q4. The study  applies Autoregressive Distributed Lag (ARDL)  bounds test, concluding the existence of a  long-run co-integrating relationship between  sector-specific GDP with stock market indices  and financial development in India. The  granger causality tests conclude the existence  of a bi-directional causality running between  financial development and sector-specific  economic growth. The study found that there  exists a two-way causality between sectoral  stock market development and sector-specific  economic growth only in the services sector  while only a unidirectional causality runs  from stock market growth to GDP growth in  the manufacturing sector, and there exists no  causality in the utility sector.
Keywords: Financial development; stock market; Autoregressive distributed lag (ARDL) bounds test; Granger causality; economic growth